EDUKASI UNTUK PENANGGULANGAN KEKERASAN SEKSUAL DAN FISIK PADA ANAK DI KAMPUNG KB BANGAU PUTIH KOTA PADANG - Irwan Irwan; Widya Kurnia; Elvawati Elvawati (CV. Multi Kreasi Media, 2022)
−This service aims to provide education about the prevention of sexual and physical violence against children in the KB Bangau Putih Village, Padang City. This service activity was carried out in the Kampung KB Bangau Putih, Padang City. Actors involved in the service are the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) and academics. The model of service in this activity is socialization and discussion. The implementation method starts from field observations, in-depth interviews and is equipped with field data in the form of documents. Data analysis used the Miles and Huberman model by collecting data, presenting data and drawing conclusions. The results of this service show that the participants are interested and enthusiastic in this service. The curiosity about cases of violence is getting higher and it creates a better sense of affection for children. the participants gain knowledge to keep children's association better and gain high motivation in educating children.